2017
DOI: 10.1097/md.0000000000006121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertonic saline on postoperative complications for patients undergoing upper gastrointestinal surgery

Abstract: The aim of this study was to explore the impact of 3% hypertonic saline (HS) intragastric administration for patients who underwent upper gastrointestinal surgery.During the postoperative period, 3% HS has been suggested as a means to improve the intestinal edema and reduce gastrointestinal complications.The medical records of 111 patients with HS intragastric administration following upper gastrointestinal surgery and 268 patients, served as control, were reviewed retrospectively. Propensity score matching wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 29 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…However, it is to be noted that the decision of patient's discharge in our institute is difficult to control and is governed by many factors such as surgeon preference and the distance of patient's residence. Analogous to these results are those reported by Hong et al [9], where they found that the mean length of hospital stays in patients with HS treatment were similar to patients without HS treatment. The rate of postoperative complications was higher in the LR group, and this could be attributed to the larger volumes infused in this group.…”
Section: Timesupporting
confidence: 88%
See 4 more Smart Citations
“…However, it is to be noted that the decision of patient's discharge in our institute is difficult to control and is governed by many factors such as surgeon preference and the distance of patient's residence. Analogous to these results are those reported by Hong et al [9], where they found that the mean length of hospital stays in patients with HS treatment were similar to patients without HS treatment. The rate of postoperative complications was higher in the LR group, and this could be attributed to the larger volumes infused in this group.…”
Section: Timesupporting
confidence: 88%
“…Hong et al . [ 9 ] found that intra-gastric administration of 3% HS for patients who underwent upper GI surgery improved the intestinal edema and reduced the incidence of anastomotic leakage and post-operative ileus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations